2012
DOI: 10.1016/j.jdiacomp.2012.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of demographic factors and cardiovascular risk factor control among U.S. adults with type 2 diabetes by insulin treatment classification

Abstract: Aims Data on glucose and cardiovascular disease (CVD) risk factor control among persons with type 2 diabetes mellitus (DM) according to insulin treatment status are lacking. We examined DM control, risk factors, and comorbidities among U.S. persons according to insulin treatment status. Methods In the U.S. National Health and Nutrition Examination Surveys 2003–2006, we examined in 10,637 adults aged ≥30 with type 2 DM the extent of control of A1c, LDL-C, HDL-C, triglycerides, and blood pressure (BP) and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 29 publications
3
40
2
1
Order By: Relevance
“…This finding concurs with recent studies which reported that blood pressure control is associated with the prevalence of diabetes [5,12,25], especially for women [26]. Also, the prevalence of diabetes for both men and women with serum triglyceride levels of≥ 135 mg/dL appears to have increased more rapidly than for men and women with a triglyceride level of <135 mg/dL.…”
Section: Discussionsupporting
confidence: 92%
“…This finding concurs with recent studies which reported that blood pressure control is associated with the prevalence of diabetes [5,12,25], especially for women [26]. Also, the prevalence of diabetes for both men and women with serum triglyceride levels of≥ 135 mg/dL appears to have increased more rapidly than for men and women with a triglyceride level of <135 mg/dL.…”
Section: Discussionsupporting
confidence: 92%
“…The difficulty of attaining the triple endpoint goal, with its potential metabolic improvements, in patients with type 2 diabetes is well documented, 11,12 so this substantial improvement 2 years after gastric bypass surgery is encouraging. The ADA triple endpoint is aimed at treating the key attributes of the metabolic disturbance of diabetes, with the goal of reducing risk of macrovascular and microvascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…Achievement of triple endpoint control has proved remarkably difficult, with typical population groups reaching this goal roughly only 10% of the time. 11,12 However, in the first year of the DSS, 49% of participants randomly assigned to Roux-en-Y gastric bypass reached the triple endpoint goal compared with 19% of the participants randomly assigned to treatment with intensive lifestyle and medical management. 9 …”
Section: Introductionmentioning
confidence: 99%
“…In our study, T2DM was defined as any of the following: (1) a fasting glucose ≥ 6.6 mmol/L (126 mg/dL) after a 12-h fast, (2) non-fasting glucose ≥ 11.1 mmol/L (200 mg/dL), (3) use of oral anti-diabetes agents or (4) being told by a doctor they had diabetes, with the requirement of age at diagnosis of age 30 years or older, a standard for past NHANES studies involving DM. 11,13 …”
Section: Methodsmentioning
confidence: 99%
“…9 However, despite guidelines for stringent control of such risk factors, the proportion of patients managed to target is still suboptimal. 10,11 …”
Section: Introductionmentioning
confidence: 99%